Hubungan Pengetahuan Ibu Dengan Pemberian Asi Ekslusif di Wilayah Kerja Puskesmas Gurilla Kecamatan Siantar Sitalasari Kota Pematang Siantar Tahun 2022 - Nurayana Rismauli; Rosmega , Rosmega; Zulkarnain Batubara (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
Exclusive breastfeeding is giving only breast milk without any other additional food until the baby is 6 months old except for vitamins and medicine. Breast milk is produced due to the influence of the hormones prolactin and oxytocin after the birth of the baby. The first breast milk that comes out is called colostrum and contains lots of IgA immunoglobin which is good for defending the baby's body against disease. This research is a quantitative analytical survey research with a cross sectional approach taken using total sampling techniques. There were 4 respondents. The results from the researchers were that the majority of respondents had good knowledge about exclusive breastfeeding, 22 respondents (66.9%). From the results of data analysis using the Fisher's Exact test, it was obtained that the P-Value was <0.05 (0.004). The conclusion from the results of this research is that there is a relationship between maternal knowledge and the provision of exclusive breast milk in the working area of the Gurilla Health Center, Pematang Siantar City due to the level of maternal knowledge about The majority of exclusive breastfeeding in the working area of the Gurilla Community Health Center, Siantar Sitalasari District, Pematang Siantar City is good.